Chemical strategies for the covalent modification of filamentous phage - Bernard, Jenna M. L.; Francis, Matthew B. (Frontiers in Microbiology, 2014)
Historically filamentous bacteriophage have been known to be the workhorse of phage display due to their ability to link genotype to phenotype. More recently, the filamentous phage scaffold has proved to be powerful outside the realms of phage display technology in fields such as molecular imaging, cancer research and materials and vaccine development. The ability of the virion to serve as a platform for a variety of applications heavily relies on the functionalization of the phage coat proteins with a wide variety of functionalities. Genetic modification of the coat proteins has been the most widely used strategy for functionalizing the virion; however complementary chemical modification strategies can help to diversify the range of materials that can be developed. This review emphasizes the recent advances that have been made in the chemical modification of filamentous phage as well as some of the challenges that are involved functionalizing the virion.